A Genetic and Metabolomic Perspective on the Production of Indole-3-Acetic Acid by Pantoea agglomerans and Use of Their Metabolites as Biostimulants in Plant Nurseries - Luziatelli, Francesca; Ficca, Anna Grazia; Bonini, Paolo; Muleo, Rosario; Gatti, Lorenzo; Meneghini, Massimiliano; Tronati, Michele; Melini, Francesca; Ruzzi, Maurizio (Frontiers in Microbiology, 2020)
The species Pantoea agglomerans includes strains that are agronomically relevant for their growth-promoting or biocontrol traits. Molecular analysis demonstrated that the IPDC-pathway involved in the conversion of tryptophan to indole-3-acetic acid (IAA) is highly conserved among P. agglomerans strains at both gene and protein level. Results also indicated that the promoter region controlling the inducible expression of ipdC gene differs from the model system Enterobacter cloacae, which is in accordance with the observation that P. agglomerans accumulates higher levels of IAA when cells are collected in the exponential phase of growth. To assess the potential applications of these microorganisms for IAA production, P. agglomerans C1, an efficient auxin-producer strain, was cultivated in 5-L fermenter so as to evaluate the effect of the medium formulation, the physiological state of the cells, and the induction timing on the volumetric productivity. Results demonstrated that higher IAA levels were obtained by using a saline medium amended with yeast extract and saccharose, and by providing tryptophan, which acts both as a precursor and an inducer, to a culture in the exponential phase of growth. Untargeted metabolomic analysis revealed a significant effect of the carbon source on the exometabolome profile relative to IAA-related compounds and other plant bioactive signaling molecules. The IAA-enriched metabolites secreted in the culture medium by P. agglomerans C1 were used as plant biostimulants to run a series of trials at large-scale nursery farm. Tests were carried out with in vitro and ex vitro systems following the regular protocols used for large-scale plant tree agamic propagation. Results obtained with 4540 microcuttings of Prunus rootstock GF/677 and 1080 plantlets of Corylus avellana L. showed that metabolites from strain C1 improved percentage of rooted-explant, number of adventitious root formation, plant survival and quality of plant as vigor, with an increase in the leaf area between 17.5 and 42.7% compared to IBA-K-treated plants.